2021
DOI: 10.1186/s12876-021-01829-y
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional visualization improves the endoscopic diagnosis of superficial gastric neoplasia

Abstract: Background Three-dimensional (3D) technology has been used in many fields, including flexible endoscopy. We evaluated the usefulness of 3D visualization for endoscopically diagnosing superficial gastric neoplasia. Methods Twelve participants (4 novices, 4 trainees and 4 experts) evaluated two-dimensional (2D) and 3D endoscopic still images of 28 gastric neoplasias, obtained before ESD with white-light imaging (WLI) and narrow-band imaging (NBI). As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It was estimated that approximately 9%-27% of polyps/adenomas were overlooked during the conventional 2D colonoscopy procedure (5,6). In this circumstance, the 3D imaging technology was introduced to improve the PDR and ADR by highlighting the morphological characteristics of lesions, thereby providing assistance for lesion identification (10)(11)(12)(13)(14). Prior evidence indicated that 3D imaging devices could not only increase the contrast between lesions and adjacent mucosa in real time but also did not prolong the operation time (14).…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that approximately 9%-27% of polyps/adenomas were overlooked during the conventional 2D colonoscopy procedure (5,6). In this circumstance, the 3D imaging technology was introduced to improve the PDR and ADR by highlighting the morphological characteristics of lesions, thereby providing assistance for lesion identification (10)(11)(12)(13)(14). Prior evidence indicated that 3D imaging devices could not only increase the contrast between lesions and adjacent mucosa in real time but also did not prolong the operation time (14).…”
Section: Discussionmentioning
confidence: 99%
“…High-quality images are critical in keeping ophthalmologists oriented and helping them quickly judge the tissue distance in a 2-dimensional (2-D) intraocular field. Although stereoscopic endoscopy has developed in recent years [ 16 , 17 ], there are still many problems and technical challenges. [ 18 , 19 ] Hence, high-resolution microscopy images remain critical in vitreoretinal surgery.…”
Section: Discussionmentioning
confidence: 99%